Sustainable Role of Baitul Mal wat Tamwil in Expanding Islamic Microfinance Inclusion for Marginalized Communities - Nurul Hidayah; Noraziah Che Arshad; Latifah Dian Iriani; Rais Dera Pua Rawi (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2026)
This study explores the role of Baitul Mal Wat Tamwil (BMT) in enhancing access to Islamic microfinance for marginalized communities in Sorong, Southwest Papua Province. Using a qualitative case study approach, data was collected through in-depth interviews with managers and clients of three BMTs in Sorong and supplemented with user observations. The findings show that BMTs provide inclusive, Sharia-compliant financing to microenterprises, informal workers, and women-led businesses through flexible contracts such as murabahah, ijarah, qardhul hasan, and hiwalah. They adopt proactive service models and leverage community engagement to strengthen trust and outreach. One notable innovation is the establishment of local Puskopsyah (syariah cooperative-based risk-sharing center), inspired by the Islamic value of ta’awun, offering internal protection against defaults. Despite challenges such as low digital literacy and poor infrastructure, BMTs remain sustainable by relying on member-based capital, contextual product design, and strong social networks. This study contributes to the theoretical discourse on social intermediation in Islamic finance and offers practical insights for replicating community-based Islamic microfinance in other underdeveloped regions. The novelty lies in documenting a grassroots takaful initiative and human-centered financing approach that supports BMT resilience in 3T (frontier, outermost, and underdeveloped) areas. These findings align with the strategic goals of the Regional Committee for Sharia Economy and Finance (KDEKS) to foster an inclusive Islamic financial ecosystem in Papua.